2020
DOI: 10.3390/su12031128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity, Motor Performance, and Psychosocial Determinants of Active Behavior in Children: A Pilot School-Based Obesity Program

Abstract: The obesity epidemic and the decline of fitness among children highlights the need for suitable interventions designed to promote Physical Activity (PA) and healthy habits. The purpose of our pilot study was to assess the feasibility of a school-based program among overweight and obese children, by examining changes in their body composition, PA, physical fitness, and some psychosocial determinants of active behavior. An additional objective was to investigate the reciprocal relationship over time between PA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Previous school-based studies have shown inconclusive results reporting small changes or no changes in PA (for reviews, see [ 32 , 51 ]). Our results, however, are consistent with those of previous uncontrolled pilot intervention studies conducted on overweight and obese children of similar age and nationality [ 5 , 36 , 52 ], which revealed significant changes in PA and health-related fitness tests. Our findings are also in line with the results of previous studies showing the effectiveness of school-based interventions in promoting PA and physical fitness among obese children (for a review, see [ 28 ]).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous school-based studies have shown inconclusive results reporting small changes or no changes in PA (for reviews, see [ 32 , 51 ]). Our results, however, are consistent with those of previous uncontrolled pilot intervention studies conducted on overweight and obese children of similar age and nationality [ 5 , 36 , 52 ], which revealed significant changes in PA and health-related fitness tests. Our findings are also in line with the results of previous studies showing the effectiveness of school-based interventions in promoting PA and physical fitness among obese children (for a review, see [ 28 ]).…”
Section: Discussionsupporting
confidence: 92%
“…The correlations of BMI with shuttle run (positive) and standing long jump (negative) tests found in this study and in previous intervention studies [ 5 , 36 ] support the contention that overweight and obesity can have detrimental effects on motor performances [ 5 , 7 , 36 , 55 , 56 ]. Moreover, results of a pilot study with overweight and obese children showed positive associations between motor performance in the shuttle-run test and Harre circuit with unpleasant/dysfunctional states [ 36 ]. Therefore, as previous studies conducted in the context of school PE [ 57 , 58 , 59 , 60 ] suggest, an education environment that focuses on participants’ pleasant experiences is recommended in the promotion of PA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For these reasons, recent research has focused on the evaluation of multi-component clinical [ 45 ] and school-based actions [ 54 ], highlighting that programs have a greater impact if they involve the family [ 27 ]. Morano and coll.…”
Section: Discussionmentioning
confidence: 99%
“…Morano and coll. [ 54 ] showed that school programs may have sustainable benefits in reducing adiposity indicators and improving exercise adherence, physical fitness, and psychological well-being. For previously discussed reasons and to counteract unhealthy lifestyle habits in Italian children [ 25 ], particularly low PA level, we developed the school-based project “Improving Umbrian kids’ healthy lifestyle”.…”
Section: Discussionmentioning
confidence: 99%